The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1158/1078-0432.ccr-14-2422
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Pharmacokinetic and Pharmacodynamic Study of the Dual m-TORC 1/2 Inhibitor AZD2014

Abstract: Purpose: AZD2014 is a novel, oral, m-TORC 1/2 inhibitor that has shown in vitro and in vivo efficacy across a range of preclinical human cancer models.Experimental Design: A rolling six-dose escalation was performed to define an MTD (part A), and at MTD a further cohort of patients was treated to further characterize toxicities and perform pre-and posttreatment biopsies (part B). AZD2014 was administered orally twice a day continuously. Flow cytometry, ELISA, and immunohistochemistry were used to quantify phar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 25 publications
7
91
1
Order By: Relevance
“…Importantly, at the maximum tolerated dose (MTD), the authors also demonstrated reduced levels of phosphorylated S6 (∼20%-100%) in all evaluable posttreatment biopsies and reduction of phosphorylated AKT levels (20%-50%) in 3/4 assessable posttreatment biopsies. 82 In addition to these proof-of-mechanism PD biomarkers, proof-of-concept biomarkers such as reduction of proliferation (Ki67) and reduction in metabolism ( 18 F-FDG PET) also supported evidence of target inhibition in tumor. 82 At the MTD, five of nine patients showed reduction in Ki67 expression of 50%-100%.…”
Section: Mtor Inhibitors Allosteric Inhibitors (Rapalogues)mentioning
confidence: 94%
See 2 more Smart Citations
“…Importantly, at the maximum tolerated dose (MTD), the authors also demonstrated reduced levels of phosphorylated S6 (∼20%-100%) in all evaluable posttreatment biopsies and reduction of phosphorylated AKT levels (20%-50%) in 3/4 assessable posttreatment biopsies. 82 In addition to these proof-of-mechanism PD biomarkers, proof-of-concept biomarkers such as reduction of proliferation (Ki67) and reduction in metabolism ( 18 F-FDG PET) also supported evidence of target inhibition in tumor. 82 At the MTD, five of nine patients showed reduction in Ki67 expression of 50%-100%.…”
Section: Mtor Inhibitors Allosteric Inhibitors (Rapalogues)mentioning
confidence: 94%
“…82 In addition to these proof-of-mechanism PD biomarkers, proof-of-concept biomarkers such as reduction of proliferation (Ki67) and reduction in metabolism ( 18 F-FDG PET) also supported evidence of target inhibition in tumor. 82 At the MTD, five of nine patients showed reduction in Ki67 expression of 50%-100%. In addition, 8 of 11 patients showed a reduction of change in maximum standardized uptake value (SUV max ), with three patients attaining a partial response (30% reduction in SUV max ).…”
Section: Mtor Inhibitors Allosteric Inhibitors (Rapalogues)mentioning
confidence: 94%
See 1 more Smart Citation
“…The 3S-3-methylmorpholin is associated with perfect aqueous solubility of AZD2014 [40]. Besides interacting with active side residues few amino acids were present in close proximity Ser-2342, Ser-2165, Lys-2187 and non-conventional residues Gly-2238, Val-2240 that attacked the adenine ring in ATP for hydrogen bonding.AZD2014 is rationally designed having IC50 2.8nM and adverse effects similar to other pan-mTOR inhibitors [19].…”
Section: Docking Analysis Of Azd 2014mentioning
confidence: 99%
“…Besides being highly potent against several tumors none of ATP-competitive inhibitors entered clinical phase 3 or available commercially [2,18]. AZD2014, rationally designed pan-mTOR inhibitor currently in phase 1 of clinical trials, display higher specificity over PIKK family and exhibit better therapeutic effects against solid tumors [19][20][21]. AZD8055 the parent molecule is no longer in clinical trials and results are expected [22].…”
Section: Introductionmentioning
confidence: 99%